Treatment of pulmonary hypertension in patients with Hereditary Hemorrhagic Telangiectasia – A case series and systematic review. (June 2021) - Abston, Eric; Hon, Stephanie; Rodriguez-Lopez, Josanna; Moll, Matt; Lanuti, Michael; Farber, Harrison W.; Wilson, Kevin C.
Abstract: Rationale: Pulmonary Arterial Hypertension (PAH), a rare complication of HHT is associated with poor outcome. There are no trials to date that have investigated whether pulmonary vasodilator therapy improves hemodynamics or survival in this disease. Objective: To determine whether pulmonary vasodilator therapy improves survival, exercise capacity, or hemodynamics in HHT patients with pre-capillary PH. Methods: We performed a before-and-after observational study on a multicenter cohort of subjects with HHT-PAH who received intravenous prostanoid therapy. We then conducted a systematic review, searching Medline and EMBASE through December 2019. Studies that enrolled HHT-PAH subjects and reported treatment outcomes were selected. PROSPERO #158179. Results: Twenty-one articles were selected. Studies were before-and-after observational studies, case reports, and case series. Among all subjects with HHT-PAH, both mPAP (65 ± 19 pre-treatment vs 51 ± 16 mmHg post-treatment p = 0.04) and PVR (12 ± 6 pre-treatment vs 8 ± 4 WU post-treatment p = 0.01) improved with treatment. The mPAP improved with either oral (57 ± 17 pre-treatment versus 44 ± 13 mmHg post-treatment, p = 0.03) or intravenous (80 ± 15 pre-treatment versus 64 ± 16 mmHg post-treatment, p = 0.017) therapy. PVR also improved with either oral (10 ± 4 pre-treatment versus 6 ± 3 WU post-treatment, p = 0.004) or intravenous (17 ± 5 pre-treatment versus 10 ± 4 WU post-treatment, p = 0.04) therapy. Survival among HHT-PAH patients who received oral or intravenous therapy was not different (p = 0.2). Unadjusted survival among HHT-PAH patients was longer than that of IPAH patients (p = 0.008). There was no difference in side effects among HHT-PAH patient who received oral or intravenous therapy (p = 0.1). Conclusion: Pulmonary vasodilator therapy is effective in improving hemodynamics of subjects with HHT-PAH and was not associated with increased risk of side effects.